Conclusion [in Youth and jobs in rural Africa: Beyond stylized facts] - Mueller, Valerie; Rosenbach, Gracie; Thurlow, James (International Food Policy Research Institute, 2019)
Chapter 10 concludes by summarizing the major findings and discusses their implications for youth employment and inclusive growth in rural Africa.